Organizational Justice to Employee Innovative Work Behavior: Mediation Effect of Learning Capacity and Moderation Effect of Blue Ocean Leadership - Pujianto, Wahyu Eko; Musyaffaah, Lailatul; Supriyadi (Universitas Nahdlatul Ulama Sidoarjo, 2023)
Employee innovation has become an important factor in ensuring organisational success in a dynamic and competitive business environment. The concept of organizational justice plays an important role in promoting employee innovative work behaviour in each employee. This study aims to explore the relationship between organizational justice and employee innovative work behaviour by adding the mediating effect of learning capacity variables and the moderating effect of blue ocean leadership variables to complete the gap of previous studies. This study sampled employees with why generation criteria in East Java with a total sample of 383. Analysis using process macros Hayes model 7. The results of this study indicate that organizational justice has a significant positive effect on employee innovative work behaviour, then organizational justice has a significant negative effect on learning capacity, besides the results of the analysis also show that blue ocean leadership as a moderator variable can strengthen the relationship between organizational justice and learning capacity, learning capacity has a significant positive effect on employee innovative work behaviour, and organizational justice affects employee innovative work behavior through learning capacity